Innovative solutions to research in drying technology of food raw materials - Shutyuk, Vitaliy; Vasylenko, Sergei; Bessarab, Alexander; Vasyliv, Volodymyr (My University, 2013)
Reasons over of growing interest are brought in the processes of drying, and also some aspects of co-operation of industry and scientific university collectives in embodiment and application. The tendencies of research of processes of drying, that appear on the joint of different areas of science with the use of forward possibilities of technical process, are examined.Наведено причини зростаючого інтересу до процесів сушіння, а також деякі аспекти взаємодії промисловості й наукових університетських колективів у втіленні та застосуванні. Розглядаються тенденції дослідження процесів сушіння, що з'являються на стику різних галузей науки з використанням поступальних можливостей технічного процесу.
Keywords: drying; intensity; efficiency; power aspects; dry food foods; сушіння; інтенсивність; ефективність; енергетичні аспекти; сухі харчові продукти; кафедра теплоенергетики та холодильної техніки; кафедра технології консервування